What Are the Gains from Pension Reform? - Assar Lindbeck; Mats Persson (The Research Institute of Industrial Economics (IUI), 2000)
This paper presents a unified analytical framework for the analysis of social security reform. It discusses reform along two dimensions: Pay-As-You-Go versus fully funded on the one hand, and actuarial versus non-actuarial on the other. Making the system more actuarial entails a trade-off between less distorted work incentives and intra-generational redistribution. Increasing the degree of funding entails a trade-off between more distorted work incentives, and redistribution in favor of future generations. If a PAYGO system already has strong actuarial elements, the additional welfare gain from making it fully funded derives from the possibility of portfolio diversification.
Keywords: H55; 330; Pension reform; social security; funded pensions; work incentives; saving; Rentenreform; Umlageverfahren; Rentenfinanzierung; Kapitaldeckungsverfahren; Theorie